The effect of increased mobility on SARS-CoV-2 transmission: a descriptive study of the trends of COVID-19 in Zimbabwe between December 2020 and January 2021 - Murewanhema, Grant; Burukai, Trouble Victor; Chiwaka, Lameck; Maunganidze, Fabian; Munodawafa, Davison; Pote, William; Mufunda, Jacob (Pan African Medical Journal, 2022)
Introduction: when the first cases of COVID-19 were reported in Zimbabwe in March 2020, the local outbreak was characterised by an insidious increase in national caseload. This first wave was mainly attributable to imported cases, peaking around July 2020. By October 2020, the number of cases reported daily had declined to less than 100 cases per day signalling the end of the first wave. This pattern mirrored the global trends. In December 2020, reports of new COVID-19 variants emerged and coincided with the beginning of the second wave within the ongoing pandemic. This paper reports on the analysis conducted on the new wave of COVID-19 beginning December 2020 to January 2021. The objective of this study was to document the evolving presumptive second wave of the COVID-19 pandemic in Zimbabwe from December 2020 to January 2021.